Human resource practices and turnover intentions: A study of the hotel industry in Malaysia / Syed Haider Ali Shah - Syed Haider , Ali Shah (2017)
This study is an attempt to examine and incorporate HR practices and its relationship with turnover intentions. Moreover, there is a gap to link such HR practices with talent engagement, affective commitment and their outcomes. The first objective of the study is to investigate the impact of HR practices in reducing turnover intentions. The second objective is to examine the effect of HR practices on turnover intentions through mediating role of talent engagement (job engagement & organization engagement). The third objective is to analyze the mediating role of affective commitment between HR practices and turnover intentions. Based on the social exchange theory, an integrated model with three bundle of HR practices (motivation enhancing, empowerment enhancing, and skills enhancing) predicting variables, three mediating variables (job engagement, organization engagement and affective commitment) and one dependent variable, turnover intentions, is examined in this study. First, relevant dimensions of HR practices are identified from literature, where 16 dimensions of these three HR practices are selected with the help of expert survey. Based on this, the study develops a close ended questionnaire. Data was collected from 51 hotels (three star, four star and five star) which are registered with Malaysia Association of Hotels, 2014. The respondents (the line and middle line manages) are identified as the locus of talent resulting in a total of 425 managers with the response rate of 75%. This study applied the structural equation modeling technique to investigate the direct effects of HR practices (overall and dimensions) and indirect effects (through talent engagement and affective commitment) on turnover intentions. The results reveal a significant negative effect of HR practices on turnover intentions. Likewise, findings showed the mediating role of talent engagement and affective commitment between HR practices and turnover intentions. In analyzing the effects of individual HR practices, the study concludes that i) motivation enhancing practices negatively effect the turnover intentions, ii) empowerment enhancing practices negatively effect the turnover intentions and, iii) skills enhancing practices positively effect on turnover intentions. This study classified and developed three bundles of HR practices which adds value to the existing body of knowledge. Moreover, before bundling the HR practices, it is necessary to consider its individual effects on turnover intentions instead of only aggregate HR practices. This study highlights the need of careful selection of skills enhancing practices with company specific training practices. Further, this empirical study has focused on the managerial level which is considered as locus of talent. This research contributes to the existing literature of HRM on managerial level rather than general employee turnover. In addition to empirical progress in the existing knowledge, this study provides the application of this proposed model in hotels in Malaysia. Therefore, hotel management may introduce intervention strategies in the form of equipping talents with the necessary meaningful job engagement and organizational engagement. Moreover, hotel management could view engagement as a broad organizational and cultural strategy. Hence, top management could develop and manage HR practices with affective commitment and talent engagement in reducing turnover intentions.